Novel methods to study interfacial layers - Mobius, D. (Dietmar); Miller, Reinhard (Studies in interface science, 2001)
This book presents a number of selected papers given at the LB9 conference, held in Potsdam, Germany, in August 2000. It is dedicated to new techniques and methodologies for studying interfacial layers. One group of manuscripts deals with the application of surface plasmons at solid interfaces, used for example in resonance spectroscopy and light scattering. New applications of various types of Atomic Force Microscopy are reported making use of various modifications of tips. A number of chapters are dedicated to light emitting diodes built with the help of LB layers. The aim of these studies is the improvement of efficiency. Electrochemical methods were described as tools for developing sensors, in particular miniaturised pH or gas sensors. The application of synchrotron X-ray and NMR techniques have been described in detail in two extended chapters. It is demonstrated how molecular information can be detected by these methods for various types of interfacial layers. This monograph, along with 130 papers that have been submitted for publication in the special issues of relevant journals, represent the proceedings of the LBP conference.